2020
DOI: 10.3389/fncel.2020.594216
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic Calcium Dynamics Along the Pain Pathway

Abstract: Astrocytes, once thought to be passive cells merely filling the space between neurons in the nervous system, are receiving attention as active modulators of the brain and spinal cord physiology by providing nutrients, maintaining homeostasis, and modulating synaptic transmission. Accumulating evidence indicates that astrocytes are critically involved in chronic pain regulation. Injury induces astrocytes to become reactive, and recent studies suggest that reactive astrocytes can have either neuroprotective or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 116 publications
(148 reference statements)
0
8
0
Order By: Relevance
“…This participation may take the form of modulating presynaptic transmitter release, or shaping the postsynaptic excitatory signal through tonic or acute release of GABA or other transmitters (Chaudhari, 2021). Indeed, the participation of astrocytes in shaping sensory signals is an area of much recent investigation (Kozlov et al, 2006;Cirillo et al, 2012;Leonard et al, 2018;Cho and Huh, 2020;Ung et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This participation may take the form of modulating presynaptic transmitter release, or shaping the postsynaptic excitatory signal through tonic or acute release of GABA or other transmitters (Chaudhari, 2021). Indeed, the participation of astrocytes in shaping sensory signals is an area of much recent investigation (Kozlov et al, 2006;Cirillo et al, 2012;Leonard et al, 2018;Cho and Huh, 2020;Ung et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, Ca 2+ entry into astrocytes includes active transport by different types of voltage gated calcium channels (VGCCs) distributed in the membrane and passive leakage [ 152 ]. Upregulation of L-type VGCCs expression in astrocytes has been shown in pathological conditions, such as those related to AD [ 153 ]. Anekonda et al [ 154 ] have demonstrated that L-type Ca 2+ current blockers can protect cells from the inductive effect of Aβ.…”
Section: The Role Of Ca 2+ Homeostasis Dysfunction...mentioning
confidence: 99%
“…Astrocytes fill the space between neurons in the nervous system, play the role of supporting and separating nerve cells, and actively provide nutrients for the brain and spinal cord, maintain homeostasis, and regulate synaptic transmission. Astrocytes can produce chemokines and cytokines, which have a bearing on neuronal receptors to promote the interaction between neurons and glial cells. IL-1β can activate astrocytes to produce an inflammatory cascade that further enhances and prolongs neuroinflammation-induced chronic pain, , so blocking IL-1R with an IL-1R antagonist may be a potential treatment for the early or late development of pain sensitivity . Various signaling molecules, protein kinases, and cell surface receptors in activated astrocytes increase, and they interact and transmit signals to each other in response to pain.…”
Section: Glial Cells In the Central Nervous System And Inflammatory Painmentioning
confidence: 99%